The pH and Total Suspended Solid with Poly Alumunium Chloride (PAC) and Alumunium Sulfate in Leachate - Moelyaningrum, Anita Dewi; Kholifah, Zainul; Pujiati, Rahayu Sri (Universitas STRADA Indonesia, 2018)
Leachate water is a liquid containing waste degradation results from polluters. PAC and Aluminum Sulfate coagulant is a big molecular weight that are able to form larger clumps form flok. The purpose of the study to see the difference a lower pH and TSS using PAC and Aluminum Sulfate in water leachate. This research is a true experiment and method using Random Design complete (RAL) with six repetitions. The sample consists of the control group (C) and treatment group (T1, T2, T3). Coagulation-Flocculation is carried out using a PAC and Aluminum Sulfate with dose 1600 mg/L (T1), 2600 mg/L (T2), and 3600 mg/L (T3) for 76 minutes. Each sample is mixed with leachate is one liter and stirred by jar test with a speed of 400 rpm for one minute (stirring quickly) and 150 rpm for 15 minutes (stirring slowly), then it only 60 minutes. After that, the results were compared with a control group. The data were analyzed using kruskal-wallis test. The results showed that Aluminum Sulfate is more effective than PAC in lowering the pH and TSS